Meningkatkan Pemahaman Kelahiran Baru melalui Kajian Teologi dan Metode Kateketika berdasarkan Yohanes 3:3-6 - Aneke; Hermanto, Yanto Paulus (SEKOLAH TINGGI TEOLOGI KIBAID MAKALE, 2024)
This study aims to improve the congregation's understanding of the concept of new birth based on John 3:3-6 through the application of the Catechetic method taken from the Pentecostal tradition. Using a qualitative approach with literature study, this study examines the theological teachings on new birth and a combination of catechetical methods from several Pentecostal figures to formulate an effective learning model. The focus of this study is on how the integration of these various methods can produce deep theological understanding and real spiritual transformation of the congregation.